Comparison of the results of modified NDVI indicator established on the basis of measurements by hyperspectral spectrometer and digital camera - Chiliński, Michał T.; Ostrowski, Marek (Ecological Questions, 2013)
Due to the lack of readily available imaging remote sensing methods that would determine the vegetation state on a local scale, an attempt was made to calculate the modified NDVI index on the basis of digital camera photography. To verify the effectiveness of the method, the digital camera and hyperspectral spectrometer results were compared. For the analysis material leaves of six different tree species from an urban area were selected and picked in four different phases of the vegetative season. The results prove that there is no significant correlation between the two methods, but they also suggest that further research on the proposed method is necessary.